Analisis Indikator Fundamental Ekonomi Daerah di Kalimatan Barat: Pertumbuhan Ekonomi, Pendapatan Perkapita dan HDI - Bariyah, Nurul (Fakultas Ekonomi dan Bisnis, UNTAN, 2015)
This study aimed to identify the profile and classification of districts and cities in West Kalimantan based on indicators of local economic fundamentals such as economic growth, per capita income and the Human Development Index (HDI). Secondary data were obtained from the BPS West Kalimantan and other related agencies for the years 2005 - 2011. In the processing of secondary data to answer the purpose, this study uses local typology analysis tools to determine the pattern and structure of economic growth in each region (Kuncoro, 2004) which divides area into four categories: (1) regions with high-income and high economic growth; (2) regions with high-income and low economic growth; (3) regions with low-income and high economic growth; and (4) regions with low income and low economic growth.The research found development gaps between the City of West Kalimantan (Pontianak and Singkawang) and other districts where both cities have high-performance in economic growth, income per capita and HDI. None of the districts that have high performance in all three indicators. 11 other districts have diverse performance. Policy development at the district and municipal level should be based on development goals on a scale of local, provincial and national levels with a convergent pattern. This will facilitate the development of the region in the future.